2016
DOI: 10.1016/j.cpr.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

What is compassion and how can we measure it? A review of definitions and measures

Abstract: The importance of compassion is widely recognized and it is receiving increasing research attention. Yet, there is lack of consensus on definition and a paucity of psychometrically robust measures of this construct. Without an agreed definition and adequate measures, we cannot study compassion, measure compassion or evaluate whether interventions designed to enhance compassion are effective. In response, this paper proposes a definition of compassion and offers a systematic review of self- and observer-rated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
717
4
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 665 publications
(775 citation statements)
references
References 41 publications
21
717
4
33
Order By: Relevance
“…In a recent major review Strauss, et al [111] suggests the following "….we propose a new definition of compassion as a cognitive, affective, and behavioral process consisting of the following five elements that refer to both self-and other-compassion: 1) Recognizing suffering; 2) Understanding the universality of suffering in human experience; 3) Feeling empathy for the person suffering and connecting with the distress (emotional resonance); 4) Tolerating uncomfortable feelings aroused in response to the suffering person (e.g. distress, anger, fear) so remaining open to and accepting of the person suffering; and 5) Motivation to act/acting to alleviate suffering.…”
Section: Approaches To Compassionmentioning
confidence: 99%
“…In a recent major review Strauss, et al [111] suggests the following "….we propose a new definition of compassion as a cognitive, affective, and behavioral process consisting of the following five elements that refer to both self-and other-compassion: 1) Recognizing suffering; 2) Understanding the universality of suffering in human experience; 3) Feeling empathy for the person suffering and connecting with the distress (emotional resonance); 4) Tolerating uncomfortable feelings aroused in response to the suffering person (e.g. distress, anger, fear) so remaining open to and accepting of the person suffering; and 5) Motivation to act/acting to alleviate suffering.…”
Section: Approaches To Compassionmentioning
confidence: 99%
“…In the literature, there appears to be a broad consensus that compassion involves feeling for a person who is suffering and being motivated to act to help them (Strauss et al, 2016). This view was reinforced during the discussion on compassion in the focus group with constituents making statements such as 'I just want to help people' (RP4, female, clerical position, late 50s); 'I get so emotional to see or discover other people's living conditions and I always feel the need to help those in need' (RP9, female, professional, early 30s).…”
Section: Compassionmentioning
confidence: 99%
“…This view was reinforced during the discussion on compassion in the focus group with constituents making statements such as 'I just want to help people' (RP4, female, clerical position, late 50s); 'I get so emotional to see or discover other people's living conditions and I always feel the need to help those in need' (RP9, female, professional, early 30s). Compassion is frequently linked to kindness, defined by the Oxford Dictionary as 'the quality of being friendly, generous, and considerate' (Strauss et al, 2016).…”
Section: Compassionmentioning
confidence: 99%
“…This may be the reason why people sometimes still expect reciprocity when they give something to others. Strauss et al (2016) talk about compassion. According to him despite widely increasing attention, the definition of compassion is still not fully agreed upon and lacks robust measure.…”
Section: Definition Of Generositymentioning
confidence: 99%
“…Three publications were found that define and give terminology related to generosity: Codrea (2014), Strauss, Baer, &Cavanagh (2016), andJensen (2016). Codrea (2014) reveals the definition of gift from an anthropological perspective, which is different from the rigid civil notion of donation.…”
Section: Definition Of Generositymentioning
confidence: 99%